IMPLEMENTASI METODE TOPSIS UNTUK PENENTUAN PROGRAM STUDI DENGAN UJIAN TULIS BERBASIS KOMPUTER - Pardede, Grace Theresia; Rika Harman (Computer Science and Industrial Engineering, 2024)
Determining the right study program for prospective students is a very important first step in the higher education journey. Along with technological developments, the computer-based written examination (UTBK) method has become an increasingly popular and efficient choice for college entrance selection. This research aims to implement the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method in determining study programs for UTBK participants. The TOPSIS method was chosen because of its ability to accommodate various complex assessment criteria and provide more objective results. This research uses UTBK score data from several participants as a case study. Criteria considered include subject grades, participant interests, and study program capacity. Each criterion is given a weight according to its level of importance.The research results show that the TOPSIS method is able to provide study program recommendations that suit the profile of each participant effectively. It is hoped that the implementation of this method can help universities in selecting study programs more accurately and fairly, as well as assisting prospective students in choosing study programs that suit their potential and interests.